Assessing Coastal Vulnerability in Finland: A Geoinformation-Based Approach Using the CVI - Lymperopoulou, Konstantina; Petropoulos, George P.; Anna Karkani; Niki Evelpidou; Detsikas, Spyridon E. (Land, 2025)
The Arctic region, one of the most vulnerable areas globally, faces severe climate change impacts, with rising sea levels and temperatures threatening local communities. Modern geoinformation tools provide a reliable, cost-efficient, and time-saving method for assessing these climate changes in Arctic coastal regions. This study focuses on Finland’s Arctic and sub-Arctic diverse coastline. The Coastal Vulnerability Index (CVI) is used to assess the vulnerability of Finland’s coastlines, using advanced geoinformatics tools. Integrating high-resolution data from EMODnet, the National Land Survey of Finland Digital Elevation Model (DEM), and physical sources, the CVI includes six input parameters: geomorphology, coastal slope, shoreline change rates, mean wave height, tidal range, and relative sea-level change. The CVI results reveal pronounced spatial variability: 37% of the coastline is classified with very low vulnerability, primarily in the southern Gulf of Finland, and some northern segments, specifically part of Lapland, exhibit minimal susceptibility to coastal hazards. Conversely, the central Gulf of Bothnia shows high vulnerability (29%), with low and moderate vulnerability zones comprising 27% and 6%, respectively, and very high vulnerability at 1%. This assessment provides essential insights for sustainable coastal management in Finland by offering a replicable model for Arctic coastal assessments. This study supports policymakers and local communities in developing targeted adaptation strategies to enhance resilience against climate-driven coastal hazards.
Keywords: arctic; Climate change; coastal erosion; EO-PERSIST; geoinformation